Elevated CPK levels after hydrazine inhalation exposure in an F16 aircraft technician. (2018) - Binyamin, Yair; Frenkel, Amit; Brotfain, Evgeni; Koyfman, Leonid; Shliom, Ori; Klein, Moti
Abstract: Hydrazine is a hazardous material that is commonly used in the pharmaceutical industry, as well as in rocket and jet fuels, including the emergency power unit of F-16 model jets. We present four ground crew technicians who were exposed to hydrazine for less than one minute, due to a voltage fall in an F-16 jet. Physical examinations were normal and none of the technicians were symptomatic for toxicity. One of the technicians had abnormal blood chemistry levels for liver and muscle enzymes: serum glutamic-oxaloacetic transaminase(SGOT)-321U/L, serum glutamate-pyruvate transaminase (SGPT)-123U/L, and creatine phosphokinase (CPK) 3300U/L. The CPK level peaked during hospitalization to 20960U/L at 36 h after the exposure, and subsequently declined. Upon release from the hospital, 48 h after the exposure, the CPK level -was 9429U/L. In repeated tests one week and one year after exposure, liver function and CPK levels were normal. We conclude that evaluation of blood tests is important, in addition to a physical examination, in asymptomatic persons following exposure to even short term highly elevated levels of hydrazine.